Rubber composition for fenders and fender using the same
Patent Information
- Application Number
- JP2023124604
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-31
- Publication Date
- 2025-02-13
AI Technical Summary
【0012】 本発明によれば、加工性、伸び、および座屈しやすさに優れる防舷材が得られる防舷材用ゴム組成物を提供することができる。本発明によれば、加工性、伸び、および座屈しやすさに優れる防舷材を提供することができる。
Smart Images

Figure 2025020954000003 
Figure 2025020954000001 
Figure 2025020954000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a rubber composition for a fender and a fender using the same. [Background technology]
[0002] Conventionally, rubber fenders have been used to absorb energy generated when a ship comes alongside a berthing vessel, etc. Various rubber compositions have been proposed as rubber compositions for fenders.
[0003] For example, Patent Document 1 discloses a rubber composition for a fender, which contains a crosslinkable rubber, 65 parts by mass or more and 90 parts by mass or less of carbon black per 100 parts by mass of the total amount of the rubber, and a crosslinking component for crosslinking the rubber, and the rubber contains butadiene rubber in an amount of 10 parts by mass or more and 40 parts by mass or less per 100 parts by mass of the total amount of the rubber. Patent Document 1 also discloses the use of sulfur as a vulcanizing agent to be compounded in the rubber composition for a fender. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2022-190973 A Summary of the Invention [Problem to be solved by the invention]
[0005] The reaction force of a fender increases as the amount of compression increases, but if the reaction force increases monotonically, it becomes too large and causes more damage to ships and wharves. For this reason, fenders are designed so that the reaction force decreases around a certain amount of compression. This phenomenon of a decrease in reaction force is called buckling. In addition to being easy to buckle, fenders are also required to have excellent workability (e.g., scorch resistance) and elongation. However, with conventional technology, it has been difficult to obtain a fender that has excellent workability, elongation, and ease of buckling.
[0006] The present invention has been made in view of the above circumstances, and has an object to provide a rubber composition for a fender that can provide a fender having excellent processability, elongation, and buckling resistance. Another object of the present invention is to provide a fender using this rubber composition for a fender. [Means for solving the problem]
[0007] The rubber composition for fenders of the present invention, which is able to solve the above-mentioned problems, contains a base rubber including natural rubber, carbon black, 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane, and sulfur, and is characterized in that the blended amount of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane is 1.0 part by mass or more and 3.0 parts by mass or less per 100 parts by mass of the base rubber, and the blended amount of sulfur is 0.8 part by mass or more and 2.0 parts by mass or less per 100 parts by mass of the base rubber.
[0008] The mechanism by which a fender excellent in processability, elongation and buckling resistance can be obtained by using the rubber composition for a fender of the present invention is not necessarily clear, but is thought to be as follows. The crosslink density and crosslinking form of the crosslinked rubber product change the compression curve (the curve showing the relationship between the compression rate and the reaction force), which is thought to affect the ease of buckling. The crosslink density and crosslinking form of the crosslinked rubber product are also thought to affect the elongation. The crosslink density and crosslinking form of the crosslinked rubber product are greatly influenced by the vulcanizing agent, which also affects the processability.
[0009] Regarding crosslink density, if the crosslink density is too high, the distance between the rubber molecular chains becomes too close when compressed, which makes it difficult to buckle. It also makes it difficult for the rubber to stretch. On the other hand, if the crosslink density is too low (i.e., vulcanization is not sufficient), the required fender performance cannot be achieved.
[0010] Regarding the crosslinking form, in the case of monosulfide bonds, the crosslinking structure of vulcanization becomes shorter and the distance between the rubber molecular chains becomes shorter, which is thought to increase the reaction force and make buckling less likely. On the other hand, in the case of polysulfide bonds, buckling becomes easier, but the vulcanization speed becomes too fast, which worsens scorch resistance.
[0011] In the present invention, by blending 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane, a long crosslinked chain is formed, and by adjusting the blending amounts of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane and sulfur, the crosslink density and vulcanization speed can be optimized, and the processability, elongation, and buckling resistance can be improved. Effect of the Invention
[0012] According to the present invention, it is possible to provide a rubber composition for a fender, which can provide a fender having excellent processability, elongation, and buckling resistance. According to the present invention, it is possible to provide a fender having excellent processability, elongation, and buckling resistance. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is an end view showing the appearance of a reduced-size lambda-type fender test specimen prepared to measure the buckling tendency in each example of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] <Rubber composition for fenders> The rubber composition for fenders of the present invention contains a base rubber including natural rubber, carbon black, 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane, and sulfur, and is characterized in that the blended amount of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane is 1.0 part by mass or more and 3.0 parts by mass or less per 100 parts by mass of the base rubber, and the blended amount of sulfur is 0.8 part by mass or more and 2.0 parts by mass or less per 100 parts by mass of the base rubber.
[0015] Hereinafter, the raw materials of the rubber composition for a fender of the present invention will be described.
[0016] (Base rubber) The rubber composition for a fender of the present invention contains a base rubber containing natural rubber (hereinafter sometimes simply referred to as "base rubber").
[0017] Natural rubber is made by nicking plants that produce natural rubber latex (milky liquid), recovering the latex, and coagulating the rubber components contained in the latex. It contains naturally occurring cis-1,4-polyisoprene.
[0018] Examples of plants that produce natural rubber latex include Hevea brasiliensis and Hevea serowata of the Euphorbiaceae family, Rubber tree, Panagium, and Lagos of the Mulberry family, Gum arabicum, Tragacanth, Curculionidae, Zanzibar vine, Huntsumia elastica, and Urceola of the Fabaceae family, Guayule, and Rubber dandelion of the Asteraceae family, Gutta-percha, Balata, and Sapodilla of the Sapotaceae family, Morning glory of the Asclepiadaceae family, and Eucommia of the Eucommaceae family.
[0019] The natural rubber may be a CV grade in which the rubber viscosity is stabilized by adding a viscosity stabilizer or the like to the raw latex, or a non-CV grade in which the rubber viscosity is not stabilized. These may be used alone or in combination of two or more. Among these, a CV grade having a particularly stable viscosity is preferred. The natural rubber may be either SMR (standard Malaysian rubber) or SVR (standard Vietnam rubber).
[0020] Examples of the natural rubber contained in the base rubber include various grades of natural rubber such as TSR (e.g., TSR20) and RSS (e.g., RSS3), and various deproteinized natural rubbers. RSS (Ribbed Smoked Sheet) is a natural rubber obtained by coagulating latex extracted from rubber trees, pressing it with a roll to form a sheet, and drying it with smoke. TSR (Technically Specified Rubber) is a natural rubber obtained by crushing rubber latex that has naturally coagulated in a collection cup, washing it, and molding it into a block shape and inspecting the quality. These natural rubbers may be used alone or in combination of two or more kinds. By including natural rubber in the base rubber, it is possible to impart good compression rate-reaction force characteristics to the fender.
[0021] The base rubber may contain synthetic rubber in addition to natural rubber.
[0022] Examples of the synthetic rubber include styrene butadiene rubber (SBR), polybutadiene rubber (BR), polyisoprene rubber (IR), chloroprene rubber (CR), butyl rubber (IIR), acrylonitrile butadiene rubber (NBR), and ethylene-propylene-diene rubber (EPDM). These synthetic rubbers may be used alone or in combination of two or more. The synthetic rubbers include oil-extended types in which the flexibility is adjusted by adding an extender oil, and non-oil-extended types in which no extender oil is added, and either type can be used in the present invention.
[0023] The base rubber used in the present invention preferably contains natural rubber and styrene-butadiene rubber, because the base rubber containing styrene-butadiene rubber has good processability.
[0024] Specific examples of the styrene-butadiene rubber include commercially available products such as non-oil-extended SBR1500 and SBR1502, and oil-extended SBR1723, both manufactured by Sumitomo Chemical Co., Ltd.
[0025] The content of natural rubber in the base rubber is preferably 50% by mass or more, more preferably 55% by mass or more, even more preferably 60% by mass or more, and is preferably 95% by mass or less, more preferably 85% by mass or less, and even more preferably 80% by mass or less. A natural rubber content of 50% by mass or more can impart better compression ratio-reaction force characteristics to the fender, while a content of 95% by mass or less improves processability.
[0026] When natural rubber and styrene-butadiene rubber are used in combination as the base rubber, the mass ratio of the natural rubber to the styrene-butadiene rubber (natural rubber / styrene-butadiene rubber) is preferably 1.0 or more, more preferably 1.2 or more, and preferably 19.0 or less, more preferably 9.0 or less. The total content of the natural rubber and the styrene-butadiene rubber in the base rubber is preferably 60% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more. In a preferred embodiment, the base rubber contains only natural rubber and styrene-butadiene rubber.
[0027] (Carbon Black) The type of carbon black is not particularly limited, and various carbon blacks that can function as rubber fillers (filling agents, reinforcing agents) can be used. Examples of the carbon black include furnace carbon blacks such as SAF (Super Abrasion Furnace Black), ISAF (Intermediate Super Abrasion Furnace Black), IISAF (Intermediate ISAF), HAF (High Abrasion Furnace Black), MAF (Medium Abrasion Furnace Black), FEF (Fast Extruding Furnace Black), SRF (Semi-Reinforcing Furnace Black), GPF (General Purpose Furnace Black), FF (Fine Furnace Black), and CF (Conductive Furnace Black); thermal carbon blacks such as FT (Fine Thermal Black) and MT (Medium Thermal Black); channel carbon blacks such as EPC (Easy Processing Channel Black) and MPC (Medium Processing Channel Black); and acetylene black. The carbon black may be used alone or in combination of two or more kinds.
[0028] As the carbon black, it is particularly preferable to use furnace carbon black such as SAF, ISAF, HAF, MAF, FEF, GPF, SRF, etc. These furnace carbon blacks may be used alone or in combination of two or more kinds.
[0029] Specific examples of the carbon black include the following commercially available products. From the SEAT (registered trademark) series manufactured by Tokai Carbon Co., Ltd., SEAT 9H (SAF-HS, nitrogen adsorption specific surface area: 142 m 2 / g], SEAT 9 [SAF, nitrogen adsorption specific surface area: 142 m 2 / g], SEAT 7HM [N234, nitrogen adsorption specific surface area: 126 m 2 / g], Seast 6 [ISAF, nitrogen adsorption specific surface area: 119 m 2 / g], SEAT 600 [ISAF-LS, nitrogen adsorption specific surface area: 106 m 2 / g], SEAT 5H [IISAF, nitrogen adsorption specific surface area: 99 m 2 / g], Seest KH [N399, nitrogen adsorption specific surface area: 93 m 2 / g], SEAT 3H [HAF-HS, nitrogen adsorption specific surface area: 82 m 2 / g], SEAT NH [N351, nitrogen adsorption specific surface area: 74 m 2 / g], SEAT 3 [HAF, nitrogen adsorption specific surface area: 79 m 2 / g], SEAT N [LI-HAF, nitrogen adsorption specific surface area: 74 m 2 / g], SEAT 300 [HAF-LS, nitrogen adsorption specific surface area: 84 m 2 / g], SEAT 116HM [MAF-HS, nitrogen adsorption specific surface area: 56 m 2 / g], SEAT 116 [MAF, nitrogen adsorption specific surface area: 49 m 2 / g], seast SO〔FEF, nitrogen adsorption specific surface area: 42m 2 / g], Seast V [GPF, nitrogen adsorption specific surface area: 27m 2 / g], SEAT SVH [SRF-HS, nitrogen adsorption specific surface area: 32 m 2 / g], Seest FY [SRF-HS, nitrogen adsorption specific surface area: 29 m 2 / g], SEAT S [SRF, nitrogen adsorption specific surface area: 27 m 2 / g], SEAT SP [SRF-LS, nitrogen adsorption specific surface area: 23 m 2 / g], SEAT TA [FT class, nitrogen adsorption specific surface area: 19m 2 / g]
[0030] Asahi Carbon Co., Ltd. Asahi #95 (nitrogen adsorption specific surface area: 147 m 2 / g], Asahi #80 [ISAF, nitrogen adsorption specific surface area: 115 m 2 / g], Asahi #70 [HAF, nitrogen adsorption specific surface area: 77 m 2 / g], Asahi #70L [Nitrogen adsorption specific surface area: 84 m 2 / g], Asahi AX-015 [Nitrogen adsorption specific surface area: 145 m 2 / g], Asahi F-200GS [Nitrogen adsorption specific surface area: 51 m 2 / g], Asahi #65 [Nitrogen adsorption specific surface area: 42 m 2 / g], Asahi #60HN [Nitrogen adsorption specific surface area: 48 m 2 / g], Asahi #60U [Nitrogen adsorption specific surface area: 43 m 2 / g], Asahi #55 [Nitrogen adsorption specific surface area: 26 m 2 / g], Asahi #50HG [Nitrogen adsorption specific surface area: 20m 2 / g], Asahi #52 [Nitrogen adsorption specific surface area: 28 m 2 / g], Asahi #51 [Nitrogen adsorption specific surface area: 20 m 2 / g], Asahi #50U [Nitrogen adsorption specific surface area: 27 m 2 / g], Asahi #50 [Nitrogen adsorption specific surface area: 23 m 2 / g], Asahi #35 [Nitrogen adsorption specific surface area: 24 m 2 / g], Asahi #22K [Nitrogen adsorption specific surface area: 21 m 2 / g], Asahi #15HS [Nitrogen adsorption specific surface area: 14 m 2 / g], Asahi #15 [Nitrogen adsorption specific surface area: 12 m 2 / g], Asahi #8 [Nitrogen adsorption specific surface area: 12 m 2 / g], Asahi Thermal [Nitrogen adsorption specific surface area: 24 m 2 / g]
[0031] The amount of carbon black blended is preferably 65 parts by mass or more, more preferably 70 parts by mass or more, and even more preferably 75 parts by mass or more, and is preferably 95 parts by mass or less, more preferably 90 parts by mass or less, and even more preferably 85 parts by mass or less, relative to 100 parts by mass of the base rubber. If the amount of carbon black blended is 65 parts by mass or more, the reinforcing property for the base rubber becomes better, and if it is 95 parts by mass or less, the hardness of the fender becomes more appropriate.
[0032] In the present invention, it is preferable to use in combination a carbon black having a large nitrogen adsorption specific surface area and a strong reinforcing effect on the base rubber, and a carbon black having a small nitrogen adsorption specific surface area and a weak reinforcing effect on the base rubber, because by using these carbon blacks in combination, it is easier to keep the hardness of the fender in a more appropriate range while maintaining good reinforcing effect on the base rubber.
[0033] The nitrogen adsorption specific surface area of the carbon black having a large nitrogen adsorption specific surface area is 60 m 2 / g or more is preferable, and 70m 2 / g or more is more preferable, and 80m 2 The nitrogen adsorption specific surface area of the carbon black having a large nitrogen adsorption specific surface area is, but is not particularly limited to, 120 m 2 / g or less is preferable, and 100m 2 / g or less is more preferable.
[0034] The nitrogen adsorption specific surface area of the carbon black having a small nitrogen adsorption specific surface area is 50 m 2 / g or less is preferable, and 45m 2 / g or less is more preferable, and 40m 2 The nitrogen adsorption specific surface area of the carbon black having a small nitrogen adsorption specific surface area is, but is not particularly limited to, 10 m 2 / g or more is preferable, and 20m 2 / g or more is more preferable.
[0035] The nitrogen adsorption specific surface area can be measured, for example, in accordance with JIS K6217-2:2001.
[0036] The mass ratio of the carbon black having a large nitrogen adsorption specific surface area to the carbon black having a small nitrogen adsorption specific surface area (carbon black having a large nitrogen adsorption specific surface area / carbon black having a small nitrogen adsorption specific surface area) is preferably 1.0 or more, more preferably 1.2 or more, and is preferably 1.7 or less, more preferably 1.5 or less.
[0037] (Vulcanizing agent) The rubber composition for a fender of the present invention contains 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane and sulfur as a vulcanizing agent.
[0038] In the present invention, by blending 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane, a long crosslinked chain is formed, and by adjusting the blending amounts of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane and sulfur, the crosslink density and vulcanization speed can be optimized, and the processability, elongation, and buckling resistance can be improved.
[0039] The 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane has the following structure:
[0040] [ka]
[0041] Specific examples of the 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane include commercially available products such as Vulcuren (registered trademark) manufactured by LANXESS.
[0042] The amount of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane is preferably 1.0 part by mass or more, more preferably 1.2 parts by mass or more, and even more preferably 1.5 parts by mass or more, and preferably 3.0 parts by mass or less, more preferably 2.5 parts by mass or less, and even more preferably 2.0 parts by mass or less, based on 100 parts by mass of the base rubber. If the amount of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane is 1.0 part by mass or more, the fender is more likely to buckle. If the amount of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane is 3.0 parts by mass or less, the fender is more likely to stretch.
[0043] Examples of the sulfur include powdered sulfur, oil-treated powdered sulfur, precipitated sulfur, colloidal sulfur, dispersible sulfur, etc. These sulfurs may be used alone or in combination of two or more kinds.
[0044] Specific examples of the sulfur include commercially available products such as 5% oil-treated powdered sulfur manufactured by Hosoi Chemical Industry Co., Ltd.
[0045] The amount of sulfur is preferably 0.8 parts by mass or more, more preferably 1.0 parts by mass or more, and preferably 2.0 parts by mass or less, and more preferably 1.8 parts by mass or less, based on 100 parts by mass of the base rubber. If the amount of sulfur is 0.8 parts by mass or more, the processability of the rubber composition is improved and the obtained fender is more likely to buckle. If the amount of sulfur is 2.0 parts by mass or less, the processability of the rubber composition is improved and the obtained fender is more likely to stretch. When, for example, oil-treated powdered sulfur or dispersible sulfur is used as the sulfur, the amount is the amount of sulfur itself as an active ingredient contained therein.
[0046] The rubber composition for fenders of the present invention may contain, in addition to 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane and sulfur, other vulcanizing agents (e.g., peroxide-based vulcanizing agents, etc.). However, from the viewpoint of further enhancing the effects of the present invention, it is preferable that the rubber composition for fenders of the present invention contains only 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane and sulfur.
[0047] The total amount of the vulcanizing agent is not particularly limited, but is preferably at least 1.0 part by mass, more preferably at least 1.5 parts by mass, and is preferably no more than 4.0 parts by mass, and more preferably no more than 3.5 parts by mass, per 100 parts by mass of the base rubber. If the total amount of the vulcanizing agent is within the above range, the vulcanization rate can be more appropriately controlled.
[0048] (Vulcanization accelerator) The rubber composition for a fender of the present invention preferably further contains a vulcanization accelerator.
[0049] Examples of the vulcanization accelerator include thiazole-based vulcanization accelerators such as 2-mercaptobenzothiazole and di-2-benzothiazolyl disulfide; dithiocarbamate-based accelerators such as zinc dimethyldithiocarbamate; thiuram-based vulcanization accelerators such as tetramethylthiuram disulfide (TMTD), tetrabenzylthiuram disulfide (TBzTD), and tetrakis(2-ethylhexyl)thiuram disulfide (TOT-N); sulfenamide-based vulcanization accelerators such as N-cyclohexyl-2-benzothiazylsulfenamide (CBS), N-tert-butyl-2-benzothiazolylsulfenamide (TBBS), N-oxyethylene-2-benzothiazolesulfenamide, and N,N'-diisopropyl-2-benzothiazolesulfenamide; and guanidine-based vulcanization accelerators such as diphenylguanidine, di-orthotolylguanidine, and orthotolylbiguanidine. As commercially available products, products from Sumitomo Chemical Co., Ltd., Ouchi Shinko Chemical Industry Co., Ltd., etc. can be used. These may be used alone or in combination of two or more kinds.
[0050] Specific examples of the vulcanization accelerator include the Noccela (registered trademark) series (for example, Noccela NS) manufactured by Ouchi Shinko Chemical Co., Ltd.
[0051] The amount of the vulcanization accelerator is preferably 0.5 parts by mass or more, more preferably 1.0 part by mass or more, and preferably 3.5 parts by mass or less, and more preferably 3.0 parts by mass or less, per 100 parts by mass of the base rubber, because the vulcanization rate can be more appropriately controlled if the amount of the vulcanization accelerator is within the above range.
[0052] (Other Ingredients) In addition to the above-mentioned components, the rubber composition for fenders of the present invention may further contain various additives that can be used in rubber compositions for fenders, such as vulcanization aids, plasticizers, antioxidants, waxes, colorants, tackifiers, and fillers other than the carbon black, which may be appropriately selected within a range that does not impair the object of the present invention.
[0053] [Vulcanization aid] Examples of the vulcanization aid include metal compounds such as zinc oxide, and fatty acids such as stearic acid, oleic acid, cottonseed fatty acid, etc. These vulcanization aids may be used alone or in combination of two or more kinds.
[0054] Specific examples of the vulcanization aid include commercially available products such as zinc oxide type 2 manufactured by Hakusui Tech Co., Ltd. and Tsubaki manufactured by NOF Corporation.
[0055] The amount of the vulcanization aid blended is preferably 4.0 parts by mass or more, more preferably 4.5 parts by mass or more, and even more preferably 5.0 parts by mass or more, and is preferably 8.0 parts by mass or less, more preferably 7.5 parts by mass or less, and even more preferably 7.0 parts by mass or less, per 100 parts by mass of the base rubber. If the amount of the vulcanization aid blended is within the above range, the vulcanization rate can be more appropriately controlled.
[0056] It is also preferable to use a metal compound and a fatty acid in combination as a vulcanization aid. In this case, the mass ratio of the metal compound to the fatty acid (metal compound / fatty acid) is preferably 1.2 or more, more preferably 1.5 or more, and preferably 2.5 or less, more preferably 2.3 or less. If the mass ratio of the metal compound to the fatty acid is within the above range, the effects of the present invention can be obtained more effectively.
[0057] [Plasticizer] Examples of the plasticizer include oil and liquid rubber. These plasticizers may be used alone or in combination of two or more. The liquid rubber in the present invention is a rubber that is liquid at room temperature and is not included in the base rubber.
[0058] Specific examples of the oil include commercially available products such as Process NC300SN manufactured by Sanyu Industrial Co., Ltd. and Diana (registered trademark) Process Oil PW, NH, NP, NS, NR, NM, AC, and AH manufactured by Idemitsu Kosan Co., Ltd.
[0059] Examples of the liquid rubber include liquid polybutadiene rubber, liquid polyisoprene rubber, liquid polystyrene butadiene rubber, etc. Specific examples thereof include commercially available products such as Kuraray Co., Ltd.'s Kurapren (registered trademark) LBR series, LIR series, and L-SBR series.
[0060] The amount of the plasticizer blended is preferably 5.0 parts by mass or more, more preferably 10.0 parts by mass or more, and is preferably 35.0 parts by mass or less, and more preferably 30.0 parts by mass or less, per 100 parts by mass of the base rubber, because if the amount of the plasticizer blended is within the above range, the hardness of the fender can be adjusted to a more appropriate range.
[0061] [Anti-aging agent] As the antiaging agent, various antiaging agents classified according to their main functions, such as weather-resistant antiaging agents and heat-resistant antiaging agents, can be used. Examples of the antiaging agent include amine-ketone type, aromatic secondary amine type, (mono-, bis- or poly-)phenol type, benzimidazole type, dithiocarbamate type, etc. These antiaging agents may be used alone or in combination of two or more types.
[0062] Specific examples of the antioxidant include commercially available products such as the Nocrac (registered trademark) series manufactured by Ouchi Shinko Chemical Co., Ltd.
[0063] As the antiaging agent, aromatic secondary amine-based antiaging agents are preferred, and N-phenyl-N'-(1,3-dimethylbutyl)-p-phenylenediamine is more preferred, because they have excellent effects in preventing sunlight cracking, ozone cracking, flex cracking, etc.
[0064] The amount of the antioxidant is preferably at least 2.0 parts by mass, more preferably at least 2.5 parts by mass, and even more preferably at least 3.0 parts by mass, and is preferably at most 8.0 parts by mass, more preferably at most 7.5 parts by mass, and even more preferably at most 7.0 parts by mass, per 100 parts by mass of the base rubber, because the heat aging resistance is good when the amount of the antioxidant is within the above range.
[0065] [wax] Examples of the wax include natural waxes such as animal waxes, vegetable waxes, mineral waxes, and petroleum waxes, and synthetic waxes.
[0066] Specific examples of the wax include commercially available products such as OZOACE (registered trademark) series manufactured by Nippon Seiro Co., Ltd. and SANNOC (registered trademark) series manufactured by Ouchi Shinko Chemical Industry Co., Ltd.
[0067] The amount of wax blended, per 100 parts by mass of the base rubber, is preferably 1.0 part by mass or more, more preferably 1.5 parts by mass or more, and even more preferably 2.0 parts by mass or more, and is preferably 5.0 parts by mass or less, more preferably 4.5 parts by mass or less, and even more preferably 4.0 parts by mass or less, because the ozone resistance is good if the amount of wax blended is within the above range.
[0068] The rubber composition for fenders of the present invention can be prepared, for example, by kneading the base rubber, carbon black, 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane, sulfur, and a vulcanization accelerator and other components added as necessary. The kneading method is not particularly limited, and may be performed using a known kneading machine such as an internal kneader, a kneading roll, a Banbury mixer, or a kneader. It is preferable to knead each of the above components other than the crosslinking component (vulcanizing agent such as 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane or sulfur, and then further add and knead these crosslinking components.
[0069] The rubber composition for a fender of the present invention can be suitably used, for example, for a fender that is installed on a quay or the like and used to protect a ship or the quay from impacts and friction that occur when a ship comes alongside or is moored.
[0070] <Fender> The present invention includes a fender using the rubber composition for a fender of the present invention.
[0071] The fender of the present invention can be manufactured by a conventional manufacturing method for a fender. For example, the fender can be manufactured by using the rubber composition for a fender of the present invention and combining any steps such as molding, sheet molding, assembly, and crosslinking according to the size and shape of the fender to be manufactured.
[0072] Specific examples of the fender of the present invention include the following various fenders. An arch-shaped fender (including the so-called inverted V-shaped, lambda (λ)-shaped, and beta (β)-shaped) in which a head portion that constitutes the flat impact surface on which a ship or the like comes alongside, and a pair of support legs that hang down while spreading out in the fore-and-aft direction from the head portion are integrally formed from a cross-linked product of a rubber composition for fenders. A so-called kappa (κ) type fender in which a disk-shaped head and a truncated cone-shaped support leg that hangs down while expanding radially from the head are integrally formed by a cross-linked product of a rubber composition for fenders. A so-called π-type fender comprising a head portion made of steel or the like and a pair of support legs made of a cross-linked product of a rubber composition for fenders and hanging down from the head portion while spreading out in the front-to-rear direction.
[0073] At least a part of the fender (for example, the head and the support leg) may be formed from the crosslinked product of the rubber composition for fenders of the present invention described above, but it is preferable to form at least the support leg from the crosslinked product of the rubber composition for fenders of the present invention. In particular, in the case of arch-type or kappa-type fenders, it is also a preferable embodiment to integrally form the entire fender, including not only the support leg but also the head, from the crosslinked product of the rubber composition for fenders of the present invention. EXAMPLES
[0074] The present invention will be described in detail below with reference to examples. However, the present invention is not limited to the following examples, and all modifications and embodiments that do not deviate from the spirit of the present invention are included within the scope of the present invention.
[0075] The components shown in Table 1 were mixed together in an internal mixer to prepare a rubber composition.
[0076] [Table 1]
[0077] The components in Table 1 are as follows. Natural rubber: TSR20 Styrene butadiene rubber: SBR1502 (non-oil extended type) manufactured by Sumitomo Chemical Co., Ltd. Carbon black (HAF grade): Seast 3 manufactured by Tokai Carbon Co., Ltd. (nitrogen adsorption specific surface area: 79 m 2 / g) Carbon black (GPF grade): Seast 3 manufactured by Tokai Carbon Co., Ltd. (nitrogen adsorption specific surface area: 27 m 2 / g) 1,6-Bis(N,N-dibenzylthiocarbamoyldithio)hexane: Vulcuren manufactured by LANXESS Sulfur: 5% oil-treated powdered sulfur from Hosoi Chemical Industries Vulcanization accelerator: Noccela NS (sulfenamide vulcanization accelerator) manufactured by Ouchi Shinko Chemical Co., Ltd. Zinc oxide: Two types of zinc oxide manufactured by Hakusui Tech Stearic acid: Tsubaki made by NOF Corporation Plasticizer: Sanyu Industrial Process NC300SN Anti-aging agent: Nocrac 6C (aromatic secondary amine-based anti-aging agent) manufactured by Ouchi Shinko Chemical Co., Ltd. Wax: Ozoace 0355 by Nippon Seiro [Evaluation method]
[0078] <Workability (scorchability)> According to JIS K6300-1:2013 "Unvulcanized rubber-physical properties-Part 1: Determination of viscosity and scorch time using a Mooney viscometer", the unvulcanized rubber composition for fenders was heated at 130°C while rotating the rotor to measure the Mooney viscosity, and the time when the Mooney viscosity increased by 10M from the minimum value was recorded as the scorch time (st10). The scorch time of rubber composition for fenders No. 6 was set as 100%, and the values of the rubber compositions for fenders prepared in each example in Table 1 were expressed as an index. Those with a scorch time of 90 to 150% were evaluated as "○" (good processability), and those with a scorch time of less than 90% or more than 150% were evaluated as "×" (poor processability).
[0079] <Elongation (breaking elongation)> The rubber composition for fenders was used to produce a vulcanized rubber sheet with a thickness of 2 mm, length of 340 mm, and width of 80 mm by press crosslinking at 140°C. A test piece (dumbbell-shaped No. 3) was produced from the vulcanized rubber sheet produced according to JIS K6251:2017 "Vulcanized rubber and thermoplastic rubber - Determination of tensile properties". A tensile test (test speed 500 mm / min) was performed on this test piece using a tensile tester to measure the breaking elongation. The breaking elongation of the vulcanized rubber sheet of the rubber composition for fenders No. 6 prepared in each example in Table 1 was expressed as an index, with the breaking elongation of the vulcanized rubber sheet of the rubber composition for fenders No. 6 being taken as 100%. A value of 75% or more was evaluated as "○" (good elongation), and a value of less than 75% was evaluated as "×" (poor elongation).
[0080] <Easy buckling> A reduced-size lambda-type fender specimen 1 having the end face shape shown in Fig. 1 was prepared using the rubber composition for fenders. That is, a head 3 constituting a planar impact surface 2, a pair of support legs 4 hanging down from the head 3 while spreading in the front-rear direction, and a mounting flange 5 connected to the lower end of the support legs 4 and projecting outward were integrally formed from the rubber composition for fenders, and then press-crosslinked at 140°C to prepare the reduced-size fender specimen 1. The dimensions of each part were width W1 of the head 3 of 65 mm, height H of 100 mm, and width W2 between the tips of the flanges 5 of 150 mm. The prepared fender reduced specimens were subjected to a compression test using a compression tester, with the maximum compression amount being 52.5% of the height H, under standard test temperature (23°C), at a speed of 15 mm / min in the height direction, three times with a 3-minute interval between each test, and the compression ratio at the third compression and the applied load (reaction force) were measured. From the maximum load and the minimum load after the maximum load, the minimum load / maximum load was calculated as the buckling index (1 or less indicates buckling). The buckling index of the reduced fender specimens prepared from the rubber composition for fenders No. 6 was set as 100%, and the values of the reduced fender specimens prepared from the rubber composition for fenders prepared in each example in Table 1 were expressed as an index. Those with a buckling index of 100% or less were evaluated as "○" (easily buckled), and those with a buckling index of more than 100% were evaluated as "×" (not easily buckled).
[0081] <Overall Judgment> If the evaluation results for workability, elongation, and buckling ease were all "good," the overall judgment was "pass (good)," and if any one of the evaluation results for workability, elongation, and buckling ease was "bad," the overall judgment was "fail (bad)."
[0082] As is clear from the results in Table 1, the rubber composition for a fender of the present invention contains a base rubber containing natural rubber, carbon black, 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane, and sulfur, in which the blending amount of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane is 1.0 part by mass or more and 3.0 parts by mass or less per 100 parts by mass of the base rubber, and the blending amount of sulfur is 0.8 part by mass or more and 2.0 parts by mass or less per 100 parts by mass of the base rubber, can provide a fender that has excellent processability, elongation and buckling resistance. [Explanation of symbols]
[0083] 1: Reduced fender test specimen, 2: Impact surface, 3: Head, 4: Support leg, 5: Flange
[0084] A preferred embodiment (1) of the present invention is a rubber composition for a fender, comprising a base rubber containing natural rubber, carbon black, 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane, and sulfur, wherein the amount of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane is 1.0 part by mass or more and 3.0 parts by mass or less per 100 parts by mass of the base rubber, and the amount of sulfur is 0.8 part by mass or more and 2.0 parts by mass or less per 100 parts by mass of the base rubber.
[0085] A preferred embodiment (2) of the present invention is the rubber composition for a fender according to the embodiment (1), wherein the base rubber further contains a styrene-butadiene rubber.
[0086] A preferred embodiment (3) of the present invention is the rubber composition for a fender according to embodiment (1) or (2), wherein the content of natural rubber in the base rubber is 50% by mass or more and 95% by mass or less.
[0087] A preferred embodiment (4) of the present invention is the rubber composition for a fender according to any one of embodiments (1) to (3), in which the amount of carbon black blended is 65 parts by mass or more and 95 parts by mass or less per 100 parts by mass of the base rubber.
[0088] A preferred embodiment (5) of the present invention is the rubber composition for a fender according to any one of the embodiments (1) to (4), further comprising a vulcanization accelerator.
[0089] A preferred embodiment (6) of the present invention is a fender using the rubber composition for a fender according to any one of the embodiments (1) to (5).
[0090] A preferred embodiment (7) of the present invention is a fender formed as an integral whole from a crosslinked product of the rubber composition for a fender according to any one of the embodiments (1) to (5).
Claims
1. A rubber composition for a fender comprising a base rubber containing natural rubber, carbon black, 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane, and sulfur, wherein the blended amount of 1,6-bis(N,N-dibenzylthiocarbamoyldithio)hexane is 1.0 part by mass or more and 3.0 parts by mass or less per 100 parts by mass of the base rubber, and the blended amount of sulfur is 0.8 part by mass or more and 2.0 parts by mass or less per 100 parts by mass of the base rubber.
2. The rubber composition for a fender according to claim 1 , wherein the base rubber further contains a styrene-butadiene rubber.
3. 2. The rubber composition for a fender according to claim 1, wherein the base rubber has a content of natural rubber of 50% by mass or more and 95% by mass or less.
4. 2. The rubber composition for a fender according to claim 1, wherein the compounding amount of carbon black is 65 parts by mass or more and 95 parts by mass or less per 100 parts by mass of the base rubber.
5. The rubber composition for a fender according to claim 1, further comprising a vulcanization accelerator.
6. A fender using the rubber composition for fenders according to any one of claims 1 to 5.
7. A fender formed as a whole from a crosslinked product of the rubber composition for fenders according to any one of claims 1 to 5.
Citation Information
Patent Citations
Rubber composition for fender, and fender using the same
JP2022190973A
Cited By
Rubber composition for fenders and fenders using the same
JP2026166384A
Rubber composition for fenders and fenders using the same
JP2026171670A